MEMBACA LIGHTING & MODEL POSE FOTOGRAFI DALAM COVER MAJALAH (Studi Majalah ELLE Indonesia) - Aziz, Abdul; Felix, John; Sonia, Candy Reggi (Seni Media Rekam ISI Surakarta, 2017)
This research focuses on the cover of Elle Indonesia fashion magazine. Characteristics of ElleIndonesia magazine appear on the front cover with a photo model of a woman, her face isamong the brands of Elle Indonesia. Research on the cover model in this magazine aims tounderstand the meaning contained in it through observing aspects of photographic technicalboth lighting and styling (pose) model.The research method used is qualitative research withvisual methodology model.The analysis using semiotics analysis Roland Barthes, to know thecharacteristics of images and findings on the level of visual effects so as to see the relationbetween the meaning with things hidden in the picture as the vizualisation of connotationaspects.Keywords: Photography, lighting, pose, model, Semiotics, and magazine